Pengaruh Persepsi Manfaat, Persepsi Kemudahan Penggunaan, dan Tingkat Kepercayaan Pada Minat Menggunakan Uang Elektronik - Pratama, Andhika Bayu; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 27 No 2 (2019)DO - 10.24843/EJA.2019.v27.i02.p04, 2019)
This study uses a survey by distributing questionnaires. The population in this study were all students of the 2015 afternoon class which numbered 493 people. The sample in this study was determined using a nonprobability sampling technique with an incidental sampling approach. Based on the calculation using Slovin formula, the sample amounted to at least 83 people. This study uses multiple linear regression analysis techniques. Based on the results of the analysis it was found that percieved usefulness, percieved ease of use, and trust had a positive and significant effect on the interest of regular 2015 afternoon students of the Faculty of Economics and Business, Udayana University to use e-money. Keywords : TAM, perceived usefulness, perceived ease of use, trust, interest, e-money